Differential Expression of Monocarboxylate Transporter 1 and Ancillary Protein CD147 in Red Blood Cells of Show Jumping Horses - Feringer Júnior, Walter Heinz [UNESP] (2017)
We compare the expression levels of the lactate transporter complex consisting of the lactate transporter, monocarboxylate transporter 1 (MCT1), and its ancillary protein, cluster of differentiation 147 (CD147), in the membranes of red blood cells (RBCs) from two breeds of jumping horses and associate the expression levels of these proteins with their jumping ability. The expression levels of MCT1 and CD147 proteins on the membranes of RBCs collected from 30 show jumping horses of two different breeds were quantified: the Brazilian Sport Horses (n = 17) and the European Warmbloods (n = 13). The levels of MCT1 and CD147 in the RBC membranes were measured by western blot using horse-specific antibodies. Statistical analyses included unpaired Student t test and chi-squared test. According to the expression levels of MCT1 and CD147 proteins, 88% of the Brazilian Sport Horses were categorized as high lactate transporters (HTs) and the remaining 12% as low lactate transporters (LTs). The opposite was found for the European Warmbloods, where most animals (77%) were classified as LTs and the remaining animals (23%) were classified as HTs. Brazilian Sport Horses express statistically significantly higher levels of CD147 and MCT1 than European Warmbloods. The classification of horses considering the expression of proteins involved in the ability to transport lactate through the complex MCT1-CD147 seems to be breed dependent, with horses that are able to jump higher obstacles showing lower expression of the MCT1-CD147 complex in their RBCs.